Commentary: Early father–infant interaction and externalizing behaviors – a response to Ramchandani et al. (2013). (24th October 2012) - Shaw, Daniel S.
<x xml:space="preserve">Abstract</x> Many researchers have attempted to uncover the precise contribution of fathers to childrearing in relation to both young and older children's development during the past five decades (Lamb, 1975), including during the infancy period (Parke & O'Leary. S, 1975). However, few have been able to isolate precise mechanisms by which specific types of paternal childrearing practices may be linked to specific types of prosocial and problem behavior. The current paper by Ramchandani et al. (2013) breaks new ground in identifying a precise dimension of paternal parenting during early infancy ‐ engagement ‐ and linking it to maternal reports of infant externalizing problem behavior. Importantly, this association was found after accounting for the influence of several child, paternal, and maternal characteristics, including observed maternal sensitivity. Specifically, the authors found that fathers observed to be less engaging with their 3‐month olds were reported by mothers to show fewer disruptive problems 9 months later.